ROLE AND REGULATION OF THE DEVELOPMENT OF MEDIA POLICY ANALYSIS IN INDONESIA (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The writing of this article will address three important aspects in tracking the role and regulation of the development of media policy by identifying the rules of media laws and regulations; view background of policy and internal working mechanism in policy making process; power relationships among stakeholders that have implications for citizens' rights. The location of the study is limited to the existing media in Indonesia using a descriptive research approach with qualitative methodology. The purpose of writing is expected to contribute positively to the community in understanding the complexity of media issues in Indonesia that can be used to empower groups and civil society organizations. The frame of thought of writing takes several elements, such as the practical importance of research by defining policies, mutatis mutandis (important changes have been made). As well as providing a looser view of policies greater than specific decisions, but smaller than general social movements. The results of research with major approaches in research and media analysis are often reduced and fail to recognize the natural characteristics of mass media as the public sphere and the complexity behind the performance of the mass media.